Cell viability, anti-proliferation and antioxidant activities of Sideritis syriaca, Tanacetum argenteum sub sp. argenteum and Achillea aleppica subsp. zederbaueri on human breast cancer cell line (MCF-7) - Onder Yumrutas, Serdar Oztuzcu, Mustafa Pehlivan, Nilgun Ozturk, I. Eroz Poyraz, Yusuf Ziya IÄŸci, M. Ozgur Cevik, Ibrahim Bozgeyik, Ayse Fatma Aksoy, Haydar BagÄ±s , Ahmet Arslan (Journal of Applied Pharmaceutical Science, 2015)
The breast cancer is one of the most common types of cancer. Many scientists have focused on the treatment of this disease for a long time by studying anti-cancer activities of plant extracts as well as synthetics. Lamiaceae and Asteraceae have been used in anticancer studies due to their phytochemical content. The genus Sideritis, Achillea and Tanacetumare the members of these families. Sideritis, Achillea and Tanacetum are used as herbal medication for the treatment of variety of diseases. In present study, we demonstrated the biological activity of Sideritis syriaca (SS), Achillea aleppica (AAZ) and Tanacetum argenteum (TAA) methanol extracts on cell viability of the breast cancer line MCF7. MTT (3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was used to determine the cell viability and proliferation of MCF7 cells. In a dose dependent manner, methanol extracts (0, 1, 5, 25, 100 and 250 µg/ml) of SS, AZZ and TAA were examined on MCF7, and viability of cells were determined with MTT staining. Especially, concentrations in 100 and 250 µg/ml of extracts decreased the cell viability (p
Keywords: Cancer cell line,Cell viability,Antiproliferation,Antioxidant,Sideritis,Tanacetum,Achillea.